EXPLORING ENTREPRENEURIAL MINDSET, SELF-REGULATION, AND SOCIAL CAPITAL IN ENHANCING ADAPTABILITY AND RESILIENCE OF ENTREPRENEURS AMID ECONOMIC CRISES - Rijal, Syamsu (Technopreneurship and Educational Development Review (TENDER), 2024)
This study is a qualitative literature review aiming to explore the roles of entrepreneurial mindset, self-regulation, and social capital in enhancing entrepreneurs’ adaptability and resilience during economic crises. A descriptive analysis was conducted using 26 articles selected from Google Scholar for the period 1977–2024, narrowed down from an initial 50 articles. The findings reveal that an entrepreneurial mindset fosters innovation, risk-taking, and opportunity orientation, while self-regulation enables emotional management and consistent decision-making. Social capital, through network and community support, provides access to essential resources that help entrepreneurs endure economic challenges. Case studies of SMEs in Indonesia illustrate how these three factors can be integrated to build business resilience. The study offers practical recommendations, including strengthening entrepreneurial training, improving access to technology, fostering business community development, and promoting multi-stakeholder collaboration to ensure business sustainability.